Konar-MF ™: Versatile Utility Suggests Potential to Simplify Congenital Catheterization Laboratory Inventory - Sasikumar, Navaneetha; Toshniwal, Pranoti; Sastry, Usha Mandikal Kondakarna; Bakhru, Shweta; Mahimarangaiah, Jayaranganath; Koneti, Nageshwara Rao; Kumar, Raman Krishna (Pediatric cardiology, 2025)
KONAR-MF™ device is a novel, cone-shaped, medium profile, self-expanding, double-disk, nitinol occlusive device designed for the ventricular septal defect (VSD). Due to its unique design and easy deployment from either side and multiple occlusion layers, it has also been used to occlude defects other than VSD. A retrospective review was done from 2019 to 2024 from three institutions. All patients where the KONAR-MF™ device was used other than for VSD closure were included in this study. Standard post-procedure follow-up was at 1, 6, and 12 months for all patients. 79 off-label implantations of the KONAR-MF™ device were done for conditions that included 59 shunt lesions (patent ductus arteriosus -34, coronary arteriovenous fistula -12, pulmonary arteriovenous fistula -2, systemic arteriovenous fistula -3, aortopulmonary window -3, aortopulmonary collateral -5, Fontan fenestration closures -7, Fontan antegrade pulmonary valve closures -2, Abernethy malformations -3, decompressing vein -2, and paravalvular leak -2, others 4. The median fluoroscopy time was 10 min (IQR 6-18). The median duration of hospital stay was 2 days (IQR 1-4 days). There were no significant complications. Complete occlusion at the end of the procedure was documented in 72 (91.13%) patients. At a median follow-up of 18 months (IQR 12-28 months) in all except one patient who had mild residual flow with no device-/(procedure) related complications. The unique structure and compact profile of KONAR-MF™ enable a wide range of uses in catheter-based management of various CHDs with the potential to simplify the inventory of the catheterization laboratory.